Executive functions in elite athletes - Comparing open-skill and closed-skill sports and considering the role of athletes' past involvement in both sport categories - Koch, P.; Krenn, B. (Psychology of Sport and Exercise, 2021)
Previous research documented differences in executive functions between elite athletes in different sports. It was argued that athletes in sport disciplines with higher cognitive demands (i.e., open-skill) show better executive functions than athletes in less cognitively challenging sport disciplines (i.e., closed-skill). In the current study, we aimed at detecting differences in executive functions between elite athletes in open-skill versus closed-skill sports and questioned the role of their total involvement in these sports until the age of 18 on executive functions.